"Under the sword of Damocles": psychologists relate their experience of a professional misconduct complaint. Issue 5 (4th July 2022) - Kirkcaldy, Hanlé; van Rensburg, Esmé; du Plooy, Kobus
ABSTRACT: Health practitioners run the risk of ethical board complaints or legal action against them in their professional careers. This experience can have a detrimental impact on personal wellness and professional practice. This study reports on the subjective experience of ten South African psychologists who received complaints. Semi structured interviews were conducted, and the transcripts analyzed using interpretative phenomenological analysis (IPA). The data indicates that (1) the participants experienced the effects of a complaint on an intensely personal level and (2) the experience of a complaint highlighted the challenging nature of working in the modern health care arena. The researchers hope to inform the psychological community of the emotional challenges experienced during a complaint process, to encourage a transparent discourse about the subject and muster support for practitioners during an often-isolating professional incident.